1, 3-Oxazepane-4, 7-Diones Compounds: 1H and 13C NMR High-Resolution Spectroscopy (1D and 2D). (13th February 2011) - Mohammad, AbdulKarim-Talaq; Osman, Hasnah; Yeap, Guan-Yeow
Abstract : The complete 1 H and 13 C NMR assignment of new 1, 3-oxazepane-4, 7-dione compounds has been obtained using one- and two-dimensional NMR techniques including COSY, HMQC, and HMBC experiments. The data deduced from this study show that the alkyl chain and the phenyl ring are in different planes compared to the oxazepine ring.